Understanding static and dynamic bending size-dependencies in the design of a nanofibrous scaffold. (July 2019) - Wang, Jun; Yuan, Bo; Sun, Liang; Han, Ray P.S.
Abstract: From a series of experimental measurements and supplemented by results from a computational model, we investigated the static and dynamic size dependent behaviors of a single-strand polycaprolactone (PCL) nanofiber. For the static bending, the fiber stiffness showed a dramatic increase as the fiber diameter is reduced and for the dynamic bending, the resonant frequency exhibited a very similar trend. Employing the strain gradient (SG) theory, we formulated a model that not only accurately captures the magnitude of the experimentally observed size dependent response but it is also, able to correctly predict the onset of the inverse square behavior. Both our experimental data and SG model results showed that the damping term is unaffected by the size-dependency. We introduced an experimentally calibrated fiber length scale parameter to predict the onset and rise of the size dependent response and an effective elastic modulus to characterize the stiffness increase. This understanding of the pronounced enhancement in nanofibers can be used to design a nanofibrous scaffold to keep its structural integrity intact against a sudden static pull of a seeded cell or when subjected to a dynamic loading environment from say, the pulsating peripheral blood.